Influence of Hydrothermal Temperature on the Physical Characteristics and Photocatalytics Activity of TiO2 for Degradation of Amoxicillin - Sutisna, Sutisna; Maulana, Rija Rizqi; Maulina, Wenny; Sujito, Sujito; Berlianti, Nindha Ayu; Wibowo, Edy (Jurnal Sains Materi Indonesia, 2024)
Titanium dioxide (TiO2) is a photocatalyst material widely used for environmental remediation applications. In this research, TiO2 material was synthesized using the hydrothermal method at various temperatures (150°C, 180°C, and 200°C). Based on the Fourier-transform infrared (FTIR) data, it was found that all the synthesized materials showed similar absorption peaks, and Ti-O-Ti bonds were detected, which is a characteristic of TiO2. X-ray diffraction (XRD) analysis showed that all the synthesized materials were TiO2 anatase with different crystalline sizes. The synthesized TiO2 using the hydrothermal temperature of 180°C showed the smallest crystalline size of 86.81 nm. Based on the analysis of the band gap energy, it was found that wider band gap energy was obtained at higher hydrothermal temperatures. The band gap energies of the synthesized materials are 3.18 eV, 3.19 eV, and 3.21 eV for hydrothermal temperatures of 150°C, 180°C, and 200°C, respectively. The photocatalytic activity of the three synthesized materials was tested in the photodegradation experiment of amoxicillin under ultraviolet (UV) irradiation. As a result, it was found that TiO2 synthesized at 180°C has the highest photocatalytic activity by degrading 100% of amoxicillin compounds within 120 minutes.